La utilización de la historia de las ciencias en la enseñanza de la física y la química - Solbes, Jordi; Traver, M. J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
Most recently we have assisted to a considerable increase of investigations on cons tructivi Stic approaches to Science teaching, but among all these works we rarely found detailed proposals for including the History and Philosophy of Science. In this paper we consider how to initiate this trend and which should be the aims in order to get a better Science teaching. We consider basically which the pupils’ perceptions of Science in a High School level are in order to show how we can modify them by means of introducing the History of Science under a new perspective.